Local Drivers of Extreme Upper Ocean Marine Heatwaves Assessed Using a Global Ocean Circulation Model - Marin, Maxime; Feng, Ming; Bindoff, Nathaniel L.; Phillips, Helen E. (Frontiers in Climate, 2022)
The growing threat of Marine heatwaves (MHWs) to ecosystems demands that we better understand their physical drivers. This information can be used to improve the performance of ocean models in predicting major events so more appropriate management decisions can be made. Air-sea heat fluxes have been found to be one of the dominant drivers of MHWs but their impact are expected to decrease for MHWs extending deeper into the water column. In this study, we examine the most extreme MHWs occurring within an upper ocean layer and quantify the relative contributions of oceanic and atmospheric processes to their onset and decay phases. The base of the upper ocean layer is defined as the local winter mixed layer depth so that summer events occurring within a shallower mixed layer are also included. We perform a local upper ocean heat budget analysis at each grid point of a global ocean general circulation model. Results show that in 78% of MHWs, horizontal heat convergence is the main driver of MHW onset. In contrast, heat fluxes dominate the formation of MHWs in 11% of cases, through decreased latent heat cooling and/or increased solar radiation. These air-sea heat flux driven events occur mostly in the tropical regions where the upper ocean layer is shallow. In terms of MHW decay, heat advection is dominant in only 31% of MHWs, while heat flux dominance increases to 23%. For the majority of remaining events, advection and air-sea heat flux anomalies acted together to dissipate the excessive heat. This shift towards a comparable contribution of advection and air-sea heat flux is a common feature of extreme MHW decay globally. The anomalous air-sea heat flux cooling is mostly due to an increased latent heat loss feedback response to upper ocean temperature anomalies. Extreme upper ocean MHWs coincided with SST MHWs consistently, but with lower intensity in extra-tropical regions, where the upper ocean layer is deeper. This suggests that the upper ocean heat accumulation may pre-condition the SST MHWs in these regions. Our analysis provides valuable insights into the local physical processes controlling the onset and decay of extreme MHWs.